2004
DOI: 10.1148/radiol.2331031535
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Pulmonary Nodules: Dynamic Enhanced Multi–Detector Row CT Study and Comparison with Vascular Endothelial Growth Factor and Microvessel Density

Abstract: Dynamic enhancement with multi-detector row CT shows high sensitivity and negative predictive values for diagnosis of malignant nodules but low specificity because of highly enhancing benign nodules. Extent of enhancement reflects underlying nodule angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
208
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(224 citation statements)
references
References 18 publications
14
208
2
Order By: Relevance
“…According to some studies, the malignant form of pulmonary lesions tends to expand substantially more than the benign form [26,27], and perfusion increases proportionally with size [28,29]. However, our technique of CT examination, performed to stage the lung masses, does not allow a specific evaluation of net enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, the malignant form of pulmonary lesions tends to expand substantially more than the benign form [26,27], and perfusion increases proportionally with size [28,29]. However, our technique of CT examination, performed to stage the lung masses, does not allow a specific evaluation of net enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…However, our technique of CT examination, performed to stage the lung masses, does not allow a specific evaluation of net enhancement. In fact, lung masses are usually evaluated with a perfusion or dynamic protocol, which could allow the clinician to correlate net enhancement and histotype [2931]. However, our subcategories may have been too small to infer any conclusion about this type of parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-induced angiogenesis is the process by which new blood vessels are formed from existing vessels, a process essential for both tumor growth and metastasis (16). It has been suggested that the increased perfusion of angiogenesis results in increased contrast enhancement (measured by peak and net enhancement) to a magnitude determined by the intensity of angiogenesis (13,17).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is historical precedence for using this protocol, the limited temporal sampling frequency constrains the richness of the time-attenuation characteristics of the nodules. Malignant nodules generally exhibit shorter time of peak enhancement and a higher slope of enhancement, due in part to the higher microvessel density (MVD) (13). A higher sampling frequency early in the contrast injection is needed to capture this enhancement behavior (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation